Development and validation of a measure for academic locus of control - Morelli, Mara; Cattelino, Elena; Rosati, Fau; Baiocco, Roberto; Andreassi, Silvia; Chirumbolo, Antonio (Frontiers in Education, 2023)
Previous research highlighted the significant role of locus of control in predicting academic achievement and dropout, emphasizing the need for reliable measures to identify factors that foster academic success. This study aimed to develop an academic locus of control (ALoC) measure. Participants were 432 Italian university students (69 males, 363 females) pursuing bachelor’s (N=339) and master’s (N=123) degrees in Italy. The ALoC scale resulted in two factors, internal (6 items) and external ALoC (12 items), which demonstrated satisfactory dimensionality and invariance across students’ gender and attending degree. Internal and external ALoC were, respectively, negatively, and positively associated with academic dropout. This study confirmed the importance of locus of control for academic achievement, suggesting that university programs should address students’ personal sense of failure while promoting a sense of mastery and responsibility for academic outcomes.